Code Switching And Code Mixing In Joko Widodo’s Statement - Iddun Muhammad Hattory (P-SEMART JOURNAL, 2021)
Code switching was a part of sociolinguistics which explains about switching the language from one language to others. Code mixing was a part of sociolinguistics which has meaning about mix the words, phrases or clauses. This study was aimed to describe the type of code switching and code mixing. This study was applied descriptive qualitative method. The instruments of this study were the researcher and documentation. The subject of this study was Joko Widodo. The data of this study were all words that contain Code mixing and code switching. Steps of collecting data were: (1) reading the statement president of republic of Indonesia, Joko Widodo, (2) Observing directly by writing the utterances which is contain code switching and code mixing and (3) marking the switched phrases or sentences and mixed words on the utterances. Steps of data analysis were identifying code switching and code mixing, classifying the types of code switching and code mixing, analyzing the types of code switching and code mixing, and drawing the conclusion. The results of this study showed that there was two types code switching that were inter-sentential code switching and also intra-sentential code switching. There were three types of code mixing that were insertion, alternation, and congruent lexicalization.